2015
DOI: 10.1111/are.12784
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different carbon sources addition on nutrition composition and extracellular enzymes activity of bioflocs, and digestive enzymes activity and growth performance ofLitopenaeus vannameiin zero-exchange culture tanks

Abstract: A 35-day feeding experiment was conducted to investigate the effects of different carbon sources addition on nutritional composition and extracellular enzymes activity of bioflocs, and digestive enzymes activity and growth performance of Litopenaeus vannamei juveniles (average 5.52 AE 0.21 g) in zero-water exchange culture tanks. Molasses, corn flour and wheat bran were used as carbon sources and added into the tanks to promote the development of bioflocs during the experiment. During the entire experiment, go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 39 publications
3
29
0
1
Order By: Relevance
“…The formation and development of biofloc in the water column of an aquaculture tank is likely linked to the direct assimilation of dissolved nitrogenous matter (especially ammonia nitrogen) from feed and fish excretions by heterotrophic bacteria (Schneider, Sereti, Eding, & Verreth, ; Wang et al., ); thus, levels of TAN can be controlled within recommended ranges for fish culture. In this study, no water was discharged from the biofloc tanks during the 120‐day trial period, and the three forms of inorganic nitrogen remained in the safe range for tilapia aquaculture (Luo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The formation and development of biofloc in the water column of an aquaculture tank is likely linked to the direct assimilation of dissolved nitrogenous matter (especially ammonia nitrogen) from feed and fish excretions by heterotrophic bacteria (Schneider, Sereti, Eding, & Verreth, ; Wang et al., ); thus, levels of TAN can be controlled within recommended ranges for fish culture. In this study, no water was discharged from the biofloc tanks during the 120‐day trial period, and the three forms of inorganic nitrogen remained in the safe range for tilapia aquaculture (Luo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that wheat bran, a kind of high fiber and slightly soluble substance, was poorly utilized by biofloc. The results of this study concurred with the study of Wang et al () in which adding varied levels of molasses, corn flour, and wheat bran into L . vannamei culture system could result in gradual increases of both BFV and TSS levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was possible that wheat bran, a kind of high fiber and slightly soluble substance, was poorly utilized by biofloc. The results of this study concurred with the study of Wang et al (2015) in which adding varied levels of molasses, corn flour, and wheat bran into L. vannamei culture system could result in gradual increases of both BFV and TSS levels. Some studies reported that regulating C/N ratio or adding different carbon sources could affect T-AOC = total antioxidant capacity; SOD = superoxide dismutase; GSH = reduced glutathione; GSSG = oxidized glutathione; control = without addition of molasses and wheat bran; T1 = addition of 100% molasses; T2 = addition of 50% molasses and 50% wheat bran; T3 = addition of 75% molasses and 25% wheat bran.…”
Section: Discussionmentioning
confidence: 99%
“…Biofloc technology has been applied to the farming of a variety of crustaceans, including Litopenaeus vannamei (Wang et al, ), Macrobrachium rosenbergii (Asaduzzaman et al, ), Penaeus monodon (Ahmad et al, ) and Artemia franciscana (Crab, Lambert, Defoirdt, Bossier, & Verstraete, ). However, there is currently only one study (Li, Cheng, Wang, Wang, Chen & Li, ) on the use of biofloc technology for the cultivation of crayfish.…”
Section: Introductionmentioning
confidence: 99%